Cryptocurrency Regulation Knowledge Map: A Global and Indonesian Bibliometric Analysis (2016–2025) (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study maps the regulatory landscape of financial technology (fintech), focusing on cryptocurrency regulation at both global and Indonesian levels. Cryptocurrency, one of the fastest-growing fintech instruments, functions as a virtual currency secured by cryptography. Despite lacking physical form, it is widely used for investment, transactions, and speculation, with trust supported by blockchain’s transparency and immutability. However, regulatory frameworks remain fragmented across countries. The research applies a bibliometric approach, using Bibliometrix (R Studio) for descriptive analysis and VosViewer for keyword network visualization. Data were retrieved from Scopus with the keywords “cryptocurrency regulation” and “fintech regulation,” covering 2016–2025. Findings reveal 1,178 documents from 484 sources, contributed by 4,693 authors, with an average of 7.43 authors per document and an international collaboration rate of 24.79%. The annual growth rate reaches 44.31%, with an average of 14.01 citations per document. Keyword analysis identifies four main clusters: financial regulation, green finance and sustainability, decentralized finance (DeFi), and blockchain cybersecurity. This study provides a knowledge map of regulatory evolution from conventional finance to blockchain-based fintech, offering insights for academics, regulators, and industry to balance innovation, consumer protection, and financial stability.